The Influence of Training and Supervision on Employee Work Effectiveness - Dudi Hendaryan; Sendi Widianto (Almana : Jurnal Manajemen dan Bisnis, 2022)
The effectiveness of the work of employees in the company affects the course of the company's operations and the survival of the organization itself. One measure of work effectiveness is training and supervision. This study aims to determine how much influence training and supervision have on the work effectiveness of PT. Daliatex Kusuma. The research method used is a quantitative method with a descriptive and verification approach. The sampling technique used probability sampling, the researcher distributed questionnaires to 60 respondents for data analysis. The questionnaire was tested for validity and reliability, then a classical assumption test was carried out. The data analysis used is the path coefficient analysis technique, the coefficient of determination, the t-test, and the F test. The results show that partial job training has a significant effect on the work effectiveness of employees in the polyester material production division of PT. Daliatex Kusuma then supervised partially also had a significant effect on the work effectiveness of employees in the polyester material production division of PT. Daliatex Kusuma. From the results of the simultaneous test, training and supervision have a significant effect on the work effectiveness of employees in the polyester material production division of PT. Daliatex Kusuma.